A Forensic Glance to Children’s Virtual Privacy in Web 3.0 - Erk, Mehmet Aykut; Fırat, Sunay (The Bulletin of Legal Medicine, 2020)
With the social media era considering as a turning point for communication age sharing has become unlimited. Many families have being chosen technological devices rather than a safe play area for their children. It has been considered that children is hang by a thread regarding easily accessibility and personal info via YouTube which is considered the biggest video sharing platform and another recent micro-film applications which is popular with under 18 years old children.It is necessary that children and adolescents to get connect with their peers. The children and adolescents who are lurking in online world without any guidance may join social media movements so called “trends”.The other thread which children and adolescents could face is the video-sharing sites which turned into trading sector. While children are online, their parents who have an urge to get goods from those sites give their children a chief part in those videos.In some videos, children are forced to behave unnatural regarding unmatched behaviors to their mental and physical development by their parents. Another negativity for children who have a role in these videos is destructive comments that are typed under videos. Some comments which are filled with jealousy and anger can be labeled as “cyber-bullying”Consequently, when the severe usage of YouTube and video-sharing sites because of widespread use of Internet is considered, it has been a necessity to protect children’ personal information and their privacy. The harm which is stemmed from sales policy has to be spoken by...
Keywords: YouTube; TikTok; Child; Adolescent; Neglect; Abuse